Kicking Off Social Entrepreneurship: How A Sustainability Orientation Influences Crowdfunding Success - Calic, Goran; Mosakowski, Elaine (Journal of Management Studies, 2016)
AbstractResearch generally suggests that, relative to commercial entrepreneurs, social entrepreneurs stand at a disadvantage at acquiring resources through traditional financial institutions. Yet interest in social entrepreneurship appears to be at an all‐time high. The current paper advances the argument that an innovative institutional form – crowdfunding – has emerged to address the needs of social entrepreneurs and other entrepreneurs with limited access to traditional sources of capital. To examine this, we study whether and how a sustainability orientation affects entrepreneurs’ ability to acquire financial resources through crowdfunding and hypothesize that a venture's sustainability orientation will enhance its fundraising capability. We also suggest that project legitimacy and creativity mediate the relationship between a sustainability orientation and funding success. Our analysis produces two key findings: 1) a sustainability orientation positively affects funding success of crowdfunding projects, and 2) this relationship is partially mediated by project creativity and third party endorsements.